PT AEI PREFERRED ALTERNATIVE PROJECT ON âXâ FIELD IN NEAR EXPIRATION OF PSC INDONESIA CONTRACT PERIOD REFERRING TO INVESTMENT ANALYSIS - Hartawan, Dody
PT AEI (Andalan Energy Indonesia) is one of PSC Indonesia Contractor operates in Sumatra. During contract period, Contractor has obligation to deliver oil production as per agreed target. Considering short runaway of remaining PT AEI PSC period, drilling new wells which requires high capital likely produces less profitable income. Performing workover is identified giving more profitable revenue with relatively less capital need. In “X” field, workover project to convert injector well to become producer well, named INJC project, is proposed to be profitable project in near expiration of contract period situation. This final project details analysis of INJC project which will convert 10 idle injector wells, whether it is proven to be profitable project for PT AEI from project start until end of PSC contract period. It starts by gathering and analyzing key data, performing risks and uncertainty analysis, technical analysis, capital budgeting, cash flow analysis, economic analysis, decision analysis, and sensitivity analysis. Cash flow analysis is referring to financial term under PSC, while DCF model is utilized as part of economic analysis. With average oil price forecast of US$ 57.9 per barrel, total capital requirement of US$ 3.92 million, operating expenditure of US$ 1.521 million, net cash flow of US$ 1.217 million, and WACC of 8.37%, it is recognized that INJC project can yield NPV of US$ 0.898 million, IRR of 44%, PBP of 18.74 months, DPI of 1.23, and VC of US$ 0.133 million. INJC project key economic indicators show profitable result and it is suggested to proceed.